A contextualização do tema cidade no ensino de Geografia escolar: contribuições para as práticas pedagógicas e a aprendizagem na educação básica - Basílio, Edvar Ferreira (2021)
The author of this paper comes from the principle that the everyday spaces on which the student inserts himself are afluents of multiple methodological possibilities of teaching and apprenticeship and that the concrete reality, within the urban contexts for the majority of population, needs to be included effectively on the pedagogical practices of the Basic Education. Based on this is the general objective of this research, which consists of discussing the development of pedagogical practices and of apprenticeship in Basic Education with support in the contextualization of the city theme in the curricular component of geography. The sociospatial reference is the city of Fortaleza - Ceará, with the investigative focus in the 3rd, 5th and 7th grades of elementary school. By means of qualitative approach, based in theoretical research and field research, the paper organizes itself in three main sessions, which interact and complement forming an independent and aggregated conjunct: a) Theoretical and Methodological Fundamentals: Which supports itself on the geographical categories of Landscape and Place to present the educative purpose of the student’s city; b) Field Research: Which demonstrates how the student’s city is present in the methodologies of teaching and apprenticeship of teachers of Basic Education; c) Didactic-Methodological Propositions: Which delineates, with support of the first two research stages, contributions for the promotion of urban spaces in the scholar actions. Within its conclusions, this research ascertained: That the themes about the student’s city are less highlighted in pedagogical practices; That the methodologies of teaching and apprenticeship privilege the knowledges of didathical manuals in detriment of the reality that manifests itself in the faced conjuncture; That knowledge, reading, critical interpretation and the redefinition of the sociospatial reality of the student are part of a education that orientates itself to the citizenship exercise. The panorama of sensorial, affective and relational spaces in which the apprentice incorporates himself can be the assumption to instigate the individuals to recognize themselves as individuals who detain rights, duties, responsibilities and are imbued with the capacity to intervene in the circudant horizon. The expectation is that this research motivates the acquisition of didactic-methodological strategies that encourage the search for social quality of education, since it’s believed that school is a privileged space to influence participation in community’s life and to raise awareness on the meaning of a good living in the city.